The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10551-010-0537-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Sustainability in Selecting Emerging Economy Suppliers

Abstract: social sustainability, supplier selection, emerging markets, international sourcing, stakeholder theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
266
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(278 citation statements)
references
References 143 publications
(163 reference statements)
6
266
0
6
Order By: Relevance
“…First, it responds to the call for empirical studies demonstrating how socially responsible procurement practices are adopted (Ashby et al 2012). Quantitative studies of the drivers and outcomes of social responsibility are rare (Ehrgott et al 2011;Park-Poaps and Rees 2010) and this is the first study to use structural equation modeling in order to understand how bases of power impact the adoption of socially responsible procurement practices by first-tier suppliers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it responds to the call for empirical studies demonstrating how socially responsible procurement practices are adopted (Ashby et al 2012). Quantitative studies of the drivers and outcomes of social responsibility are rare (Ehrgott et al 2011;Park-Poaps and Rees 2010) and this is the first study to use structural equation modeling in order to understand how bases of power impact the adoption of socially responsible procurement practices by first-tier suppliers.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have investigated how and why dependence impacts sustainable practice adoption in the supply chain, showing that highly dependent suppliers are more likely to adopt specific environmentally or socially responsible practices within their own firms (Awaysheh and Klassen 2010;Touboulic et al 2014). Other studies have shown that coercive pressure from powerful buyers is vital in driving socially responsible practice adoption (Ehrgott et al 2011;Fishman 2006;Huq et al 2014). What has not been investigated in this field is how different types of power use by key direct customers affect first-tier suppliers' adoption of different types of socially responsible procurement practices with their key second-tier suppliers.…”
Section: Bases Of Power Theorymentioning
confidence: 99%
“…Studies in social sustainability investigate, in their majority, critical factors and enablers (antecedents) (Clarkson, 1995;McWilliams and Siegel, 2000;Ehrgott et al, 2011;Searcy and Buslovich, 2014); and the impact of social sustainability on performance (Kolk et al, 2010;Gunasekaran and Spalanzani, 2012;Delai and Takahashi, 2013;Sebastiani et al, 2014). However, social issues and antecedents of social sustainability vary across geographic locations (Gugler and Shi, 2009;Huq et al, 2014).…”
Section: Supply Chain Social Sustainability and Dimensionsmentioning
confidence: 99%
“…The leading article on this path is the contribution by Ehrgott et al (2011). The major aim of this study is to examine how stakeholder pressures determine the extent to which focal firms consider ethical and social aspects in selecting suppliers in emerging countries.…”
Section: Stakeholders and Supplier Management In Emerging Countriesmentioning
confidence: 99%
“…On the other hand, this result clearly supports our earlier statement that ethical sourcing studies are still in the early stage focusing more on developing new theory. In fact, some of the prior studies are focused on the consequences of corporate ethical sourcing, including buyer satisfaction (Akamp and Müller 2013;Carter 2000;Kaynak and Sert 2012), supplier performance like capabilities (Carter and Jennings 2002;Ehrgott et al 2011), buyer reputation (Eltantawy et al 2009), relationship performance (Gonzalez-Padron et al 2008;Leonidou et al 2013), and supplier compliance (Jiang 2009). However, it is only lately that authors have begun to direct attention towards the financial effects of ethical sourcing.…”
Section: Implications For Future Researchmentioning
confidence: 99%